Analyses of the Causes of Common Rail Piezoelectric and Electromagnetic Injectors’ Premature Destruction in Self-Ignition Engines - Slawomir Olszowski; Jozef Buday; Jozef Kuchta; Jan Michalik (Communications - Scientific letters of the University of Zilina, 2013)
In self-ignition engines with Common Rail direct fuel injection, premature destruction of injectors has been observed. New elements are also touched by the problem. In order to solve it, a group of international experts in the area have gathered. Destroyed piezoelectric and electromagnetic injectors’ elements of BOSCH, DELPHI, DENSO, have been examined. Mechanical damages influencing electronic diagnostic signal have been presented. Some system solutions possible to perform as far as diagnostic prevention is concerned have been described. Some useful electronic diagnostic methods of fuel system, signal analysers: RMOG and ERDIA PRO, have been presented.